Design of autostereoscopic 3D display with full resolution by means of polarization gratings. (18th January 2018) - Xia, Renjie; Wang, Changshun; Pan, Yujia; Yang, Yifei; Li, Hongjing
Abstract: Autostereoscopic 3D, a kind of display technology, can give people an amazing visual experience. A design of autostereoscopic 3D display based on the polarization gratings is proposed in this paper. The designed system is placed on the outside surface of LCD. Image from two video sources which have parallax, can be alternately displayed on the LCD screen at a rate of 48 frames per second, and owing to polarization gratings, the direction of emergent light of the system can be changed which depends on the handedness of the incident light. By using the unique diffraction characteristics of the polarization gratings and fast response of liquid crystal, the image from two different video sources enters people's left and right eye respectively. Due to the existence of parallax, people can perceive depth of the image. The system is based on the time division multiplexing of LCD pixels, so there is no pixel loss and image with full resolution can be used.